2018
DOI: 10.1016/s2468-1253(18)30264-4
|View full text |Cite
|
Sign up to set email alerts
|

A core outcome set for clinical trials of chemoradiotherapy interventions for anal cancer (CORMAC): a patient and health-care professional consensus

Abstract: This is a repository copy of A core outcome set for clinical trials of chemoradiotherapy interventions for anal cancer (CORMAC): a patient and health-care professional consensus..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 34 publications
2
46
0
Order By: Relevance
“…Lastly, there are significant difficulties in comparison across trials stemming from the varying outcome definitions. We defined our clinical outcomes with advice from the CORMAC team, who recently published a core set of outcomes in ASCC 42 with the inclusion of the additional outcome colostomy-free survival due to international interest in this outcome. The CORMAC group undertook a systematic review of anal cancer trials, identifying 1192 different anal cancer outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, there are significant difficulties in comparison across trials stemming from the varying outcome definitions. We defined our clinical outcomes with advice from the CORMAC team, who recently published a core set of outcomes in ASCC 42 with the inclusion of the additional outcome colostomy-free survival due to international interest in this outcome. The CORMAC group undertook a systematic review of anal cancer trials, identifying 1192 different anal cancer outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the Delphi survey will inform a consensus meeting to finalise the COS. While other COS studies in the field of cancer17–19 may have identified similar important outcomes such as survival, it was important to consider our participants separately given the unique problems which arise with gastrectomy. These include distinctive short-term and long-term problems related to surgery such as anastomotic leak and reactive hypoglycaemia (dumping syndrome) which would not be relevant in other COS.…”
Section: Discussionmentioning
confidence: 99%
“…For the CESCOS Delphi, HCPs (82%) had a better response rate compared to the patients (55%) in round 2. This may be a reflection that most HCPs were recruited from professional organisations and patients were recruited openly from social media [21]. The importance of completing both rounds of the Delphi may not have been emphasised enough through social media.…”
Section: Discussionmentioning
confidence: 99%
“…We have adopted the "70/15" consensus definition in the protocol, which was used successfully in other COS studies [20,21] for inclusion of an outcome in the COS. However, it was partially revised for "consensus out" due to the study team's experience from other studies where outcomes were rarely voted 1-3 not important and reach criteria for exclusion after the Delphi survey [21]. This revision was done without reference to the identity of the outcomes.…”
Section: Consensus Definitionmentioning
confidence: 99%